Tari Cangget Pilangan Di Daerah Abung Selatan Kabupaten Lampung Utara: Tinjauan Koreografi - Maysa Nurfiana; Nerosti Nerosti (FBS Universitas Negeri Padang, 2021)
This study aims to describe and analyze the choreography of Cangget Pilangan Dance in Abung Selatan village of North Lampung. This research belongs to a qualitative research using descriptive analysis. The instrument used was the researcher itself and was assisted by supporting instruments such as writing tools and cameras. Types of data used were primary and secondary data. The data were collected through literature study, observation, interview, and documentation. The data analysis was done through data reduction, data modeling (displaying), and conclusions making through choreography theory by analyzing theme, motion, floor design, top design, dramatic design, dynamics, group composition, music, and dance equipment. The results show that Cangget Pilangan dance is a creation in the form of a group which uses unison composition, balance, canon, and broken. This Cangget Pilangan dance is a development of the tradition using a choreographic approach. In Cangget Pilangan dance, there are elements of dance composition consisting of themes, movements, top designs, floor designs, dramatic designs, music designs, processes, equipment and group choreography. The movements in this dance are the development of Cangget motion and new creations: the motion of tiptoe, respect, hand, rotating hand, back step, transition 1. igel, wave, transition 2. rotating hands, turning, low turning, hand span, transition 3. transition 4. transition 5. transition 6. jump, hovering grab, shawl pull, gentle waves, close embarrassment, drift, ukel, worship, side ukel, front ukel, front walk, swing, open cross, and shawl cross. The floor pattern depicts creative dance that has fulfilled the elements of dance composition. The single cone dramatic design clearly depicts moderate to strong motion forces. A dramatic design clearly shows about the gentleness and manliness of the Lampung girl. The music strongly accompanies the flow of the dance movements, so it makes the dance alive and strong. The dance equipment gives a new color to the creative dance which is worked on as well as the group choreography which shows high social values in teamwork and mutual cooperation.